How to Climate Proof Water Sanitation Services for the Urban Poor - Heath, Tom; Parker, Alison; Weatherhead, E. K. (Cranfield University, 2010)
This report is based upon a 10 month project assessing the vulnerability of WSUP (Water and Sanitation for the Urban Poor) projects to climate change, converting climate change predictions into recommended adaptations. The findings are based on a literature review and field work in Kenya, Madagascar and Zambia, undertaking focus groups, stakeholder interviews and observations. This report synthesises the science of climate change, the impacts of climate change on drinking water and sanitation, how to climate proof water and sanitation services and how to adapt: